2012
DOI: 10.1111/1574-6941.12017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant host species and plant community richness on streptomycete community structure

Abstract: We investigated soil streptomycete communities associated with four host plant species (two warm season C4 grasses: Andropogon gerardii, Schizachyrium scoparium and two legumes: Lespedeza capitata, Lupinus perennis), grown in plant communities varying in species richness. We used actinobacteria-selective PCR coupled with pyrosequencing to characterize streptomycete community composition and structure. The greatest pairwise distances between communities were observed in contrasts between monocultures of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
(54 reference statements)
0
40
1
Order By: Relevance
“…In the present study, the complexity of soil–plant–microbial system could explain the large non-significant potato tuber among treatments with increased in continuous cropping years. Bakker et al (2013) noted that potato competent microbes important for crop productivity is determined by site, cultivar and soil type that influence microbial community and consequently for better soil quality and crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the complexity of soil–plant–microbial system could explain the large non-significant potato tuber among treatments with increased in continuous cropping years. Bakker et al (2013) noted that potato competent microbes important for crop productivity is determined by site, cultivar and soil type that influence microbial community and consequently for better soil quality and crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…3A and 3E), which are generally known to decompose recalcitrant polymers in soils (17). A recent study of Zimmerman sand created by glacial outwash indicated that host plant species and increasing plant richness altered the composition of Streptomyces communities, which were the most abundant among the Actinobacteria (1). Similar to this finding, in our study, the family-level composition of Actinobacteria in the volcanic deposits was also found to differ distinctly at different sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also in natural grasslands, the diversity of neighbouring plants has been found to affect Streptomyces spp. and fungal communities in soil at the base of specific plant species (Bakker et al 2013;LeBlanc et al 2014). Whereas the fungal communities were distinctly different between two grasses and two legumes grown in monoculture, they became similar when the species where grown in mixtures.…”
Section: Indirect Neighbour Effects Via the Root Microbiomementioning
confidence: 99%